Живая шляпа: рассказы / Н.Н. Носов; ил. И. Семенова - Носов Николай Николаевич (Книги-мои друзья, 2012)
Экземпляры: ф.6 (20130430) / Инвентарный номер: 44387 / Цена: 81.00 / Авт.знак: Н 84 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6